Effects of mixed hardwoods dust on respiratory function and blood immunoglobulin levels in wood workers - Isaac E. Ennin; Festus K. Adzaku; Daniel Dodoo; Raymond Saa-Eru Maalman (Heliyon, 2024)
Background: Occupational exposure to wood dust, generated by various individual wood species, both softwood and hardwood, has been extensively documented as a causative factor for reduced lung function, frequent respiratory symptoms, and increased immunological responses in wood workers. This study explores the impact of wood dust from mixed tropical hardwood species on lung function, respiratory symptoms, and Immunoglobulin (Ig) E and G levels. Methods: A cross-sectional study was conducted among wood workers at the Accra Timber Market and a control group from the University of Ghana. Particulate matter (PM) was sampled using a Minivol Sampler set to a flow rate of 5 l/min. Respiratory symptoms were assessed using questions adapted from the British Medical Research Council (MRC) questionnaire (1960). Lung volumes and airflow rates were measured using a spirometer. Total serum IgE and IgG levels were quantified using ELISA. Results: No significant differences were observed between the wood workers and the controls for demographic variables. Wood workers exhibited a significantly higher prevalence of respiratory symptoms, particularly rhinitis, with many reporting the absence of symptoms during holidays. Lung function parameters (VC, FEV1, FEV1%, PEFR, and FEF25-75%) were significantly reduced (p < 0.05) in wood workers. A significant negative correlation was noted between lung function parameters and years of exposure to wood dust. Wood workers showed significantly elevated levels (p < 0.05) of IgG and IgE. Conclusion: The study findings suggest that exposure to mixed tropical hardwood dust induces elevated blood IgE and IgG levels, along with non-allergic respiratory function abnormalities.